Preparation of Rice Bran-Enriched Sweet Rice Wine and Its Quality Improvement Through Extrusion - Wantian Li; Teng Han; Yuxin Wen; Hao Zhang; Dandan Li (Foods)
This study aimed to improve the quality of sweet rice wine through exogenous addition of rice bran and extrusion. The effects of directly fermenting brown rice and adding rice bran on key quality indicators including alcohol content, sugar-to-acid ratio, antioxidant properties, and sensory characteristics were evaluated. Compared to direct fermentation, the exogenous addition of rice bran significantly improved overall wine quality, with 4% rice bran yielding the optimal alcohol content of 1.6% vol and sugar-to-acid ratio exceeding 40. Extrusion modified the physical structure of rice bran, improving its performance as a fermentation substrate. Consequently, both the antioxidant activity and flavor profile of the sweet rice wine were further enhanced. These findings provide valuable theoretical insights for the development of high-quality whole-grain foods.